Asean Value: Analisis Respon Negara asing dalam Kebijakan Penenggelaman Kapal pada Masa Pemerintahan Jokowi Tahun 2014 – 2018 - Nadhila Widya Normasari; Reni Windiani (Journal of International Relations Diponegoro, 2022)
One of the problems that harms Indonesia the most is the problem of illegal fishing practices by foreign vessels. Illegal fishing is defined as fishing activities that are not reported to the relevant fisheries authorities and fishing activities that are not regulated by laws and regulations. Hence, the role of the government in overcoming these infringing activities is very important. One form of government countermeasures is the implementation of a ship sinking policy aimed at sinking foreign ships that steal fish in Indonesian waters. The aim of this study is to determine the foreign response to the implementation of the policy of sinking ships in Indonesian waters. To analyze this, this study uses constructivism theory, specifically the concept of identity and norms. This research is an explanatory research type and a qualitative research type with data collection techniques through documentation studies, data collection techniques through analysis of existing documents. The results of this study show that foreign countries, particularly Vietnam, the Philippines, Thailand and Malaysia, responded well to the policy of austerity imposed by Indonesia. The ASEAN principles contained in the Treaty of Friendship and Cooperation (TAC) were motivated for the positive response from abroad.